Intrauterine haematomas in the first trimester and pregnancy complications - Al-Memar,M; Vaulet,T; Fourie,H; Bobdiwala,S; Farren,J; Saso,S; Bracewell-Milnes,T; De,Moor B; Sur,S; Stalder,C; Bennett,P; Timmerman,D; et al. (Ultrasound in Obstetrics and Gynecology, 2020)
OBJECTIVES: The role of intrauterine haematoma on pregnancy outcomes remains uncertain. Some studies report an association with miscarriage, whilst others refute this. The impact on long-term outcomes is not known. We aimed to assess if intrauterine haematomas detected using ultrasonography in the first trimester are associated with adverse pregnancy outcomes. METHODS: A prospective observational cohort study at Queen Charlotte's & Chelsea Hospital, London, was conducted between March 2014 and March 2016. Participants with intrauterine pregnancies were recruited and underwent serial ultrasound scans in the first trimester. Clinical symptoms, including pelvic pain and vaginal bleeding were recorded using validated symptom scores at each visit. The presence, location and size of any intrauterine haematoma seen on ultrasonography was noted. Pregnancy outcomes were obtained from hospital records. RESULTS: Of 1003 recruited participants, 268 had an intrauterine haematoma (27%). The presence of intrauterine haematoma in the first trimester was associated with preterm birth (OR 1.94; 95% CI 1.07-3.53). No association was found with miscarriage (OR 0.916; 95% CI 0.571-1.471). This was irrespective of the absolute size of the haematoma or the presence or absence of vaginal bleeding and pelvic pain. A retroplacental haematoma was associated with an increase in overall antenatal complications (P = 0.0395). CONCLUSIONS: Our data demonstrates no association between the presence of intrauterine haematoma in the first trimester and first trimester miscarriage. However, a relationship with preterm birth independent of the presence of symptoms of pain and bleeding is evident. These women should be counseled about their increased risk of preterm birth and possibly be offered increased surveillance during their pregnancies. This article is protected by copyright. All rights reserved.